UPAYA MEMBANGUN CUSTOMER ENGAGEMENT MELALUI MEDIA SOSIAL INSTAGRAM - Rohadian, Safitri; Amir, Muhammad Taufiq (Program Studi Manajemen, 2019)
Using Instagram as a marketing tool requires online shop owners to build Customer engagement with followers so that their business can be sustainable. High engagement on Instagram can help online shops increase their sales and dig up more information about consumers' desires by doing various interactions using features found on Instagram. This study describes several efforts in building Customer engagement through social media called Instagram which is carried out by four online shop owners who sell their own products. The results showed by maximizing the use of Instagram features and applied the Customer engagement concept which are Content engagement (context and communication) Media engagement, and Engagement marketing activities (collaboration and connection) are the effort to build customer engagement which turned out to sales’s increase.